2000
DOI: 10.1902/jop.2000.71.3.361
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Calprotectin Level in Gingival Crevicular Fluid With Gingival Index and the Activities of Collagenase and Aspartate Aminotransferase in Adult Periodontitis Patients

Abstract: From the present results and our previous findings, it is shown that the GCF calprotectin level significantly correlates not only with clinical indicators but also with current biochemical marker levels and that calprotectin may be a useful marker for periodontal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 46 publications
7
40
0
Order By: Relevance
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP. Our findings are consistent with the previous data showing the role of calprotectin as an inflammatory marker of periodontal disease [11,12,42,43]. Kaner et al [44] have demonstrated that GCF calprotectin levels are significantly correlated with the levels of periodontal inflammation and decreased after periodontal therapy in G-AgP patients.…”
Section: Discussionsupporting
confidence: 93%
“…Although this technique provides larger GCF volumes compared to superficial intracrevicular technique [40], in accor- dance with the suggestions of others our discussion of the data as well as studying relationship with clinical data was based on the total amount rather than concentration of the data which consider the amount of GCF collected [37,41]. The relationship between GCF calprotectin levels and several other inflammatory markers has been previously investigated and calprotectin levels were shown to be a significant contributor to host defense against infection [8,9,42,43]. The present data indicated that GCF calprotectin levels increased as the periodontal disease progresses from health to disease, but similar in G-AgP and CP.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore contend that increased plasma, salivary or faecal levels of S100A8/A9 observed in association with inflammation [2830] are aimed in part at diminishing the oxidative activation of neutrophils and protect the organism against exaggerated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In periodontitis, calprotectin levels in gingival crevicular fluid (GCF) from diseased sites are significantly higher than those in GCF from healthy sites and show positive correlations with several clinical and biochemical markers, including probing depth, interleukin 1␤, prostaglandin E2, collagenase, and aspartate aminotransferase activity (23,30). In GCF, calprotectin probably originates from pocket epithelia and inflammatory cells, including neutrophils and monocytes.…”
mentioning
confidence: 99%